Réponses

2013-12-10T23:25:29+01:00
A) x/4 + 11 = 2x - 3
11+3  = 2x-x/4
14 = (8x-x)/4
14*4 = 7x (* signifie multiplié par)
4*14/7 = x
4*2 = x
x = 8

b)7x/3 -2 = 5x/6 + 1
7x/3 - 5x/6 = 1+2
14x/6 - 5x/6 = 3
14x-5x = 3*6
9x = 18
x = 18/9
x = 2

c) (4+3x)/5 = (7x-1)/8
8(4+3x) = 5(7x-1)
32+24x = 35x-5
32+5 = 35x-24x
37 = 11x
x = 37/11

d) (6-x)/3 = (4x+1)/2
2(6-x) = 3(4x+1)
12-2x = 12x+3
12-3 = 12x+2x
9 = 14x
x= 9/14

b)7x/3 -2 = 5x/6 + 1
2*7x/6 -2*6/6 = 5x/6 + 6/6
(14x-2)/6 = (5x+6)/6
c) (4+3x)/5 = (7x-1)/8
8(4+3x)/40 = 5(7x-1)/40
(32+24x)/40 = '35x-5)/40
d) (6-x)/3 = (4x+1)/2
2(6-x)/6 = 3(4x+1)/6
(12x-2x)/6 = (12x+3)/6
merciiiii bcp !!!
de rien :)